SUPPLY CHAIN MANAGEMENT IN SMALL AND MEDIUM ENTERPRISES: SCM PRACTICES - Nurchayati, Nurchayati; Supramono, Supramono; Utami, Intiyas; Sunarto, Hari (International Journal of Supply Chain Management, 2020)
Abstract? Supply chain management (SCM) in small and medium-sized enterprises is aimed at ensuring both short- and long-term effectiveness and efficiency of these enterprises. Small and medium enterprises (SMEs) potentially make irrational decisions because of their individual limitations. Specifically, they are subject to biases, including SCM and escalation of commitment. This study investigates the causality of the interaction between SCM and experience and escalation of commitment in SMEs. This paper used a 1x2 laboratory experimental design with 69 subjects of SME owners who produced pressure-cooked milkfish in Semarang City, Central Java, Indonesia. The independent variable was SCM that consisted of two levels (high vs. low self-attribution). Business age was the proxy of experience as the mediating variable. Meanwhile, the dependent variable was escalation of commitment that was measured with investment decisions. The information on SCM was the new product development opportunity of milkfish meatball. Subjects with high SCM were informed that they had a good ability to coordinate with suppliers to develop the new products while those with low SCM were informed on the presence of the uncertain economic condition and bad luck. One-way ANOVA tested the effectiveness of randomization while independent sample test and univariate analysis of variance tested the hypotheses. The study shows that SME owners with a high self-attribution exhibit greater escalation of commitment than those with a low self-attribution. This paper also empirically finds that the interaction between SCM and experience increases escalation of commitment. By demonstrating that SCM likely affects SMEs? investment decisions, this study advises governments to take entrepreneurs? behavioral aspects into account when advocating SMEs. The financial behavior literature on escalation of commitment largely focuses on large firms in their analysis. Meanwhile, the existing phenomena show that decision-making processes in SMEs also exhibit escalation of commitment. This study investigates escalation of commitment in SMEs? investment decision making regarding SCM and experience in running businesses.